Addition of hidrolitic enzyme in commercial feed on growth and survival rate of river catfish (Hemibagrus nemurus) in recirculation system - Putra, Iskandar; ', Hariati; ', Mulyadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted to determine the dose of hidrolitic enzyme supplemented in the commercial diet that give the best performance on absolute weight, absolute length, specific growth rate, survival rate, feed efficiency, and feed convertion ratio of river catfish (Hemibagrus nemurus) in recirculation system using leavy vegetable (Ipomea reptan). The dose of enzyme was 5, 7.5, and 10 g/kg of commercial feed and no enzyme supplementation as control. Each treatment was design in triplicates. Catfish at average 5-6 cm in length were reared in a fiber tank in a density 20 fish/tank for 30 days. The best performance growth was obtained from enzyme 10 g/kg feed. The absolute weight who 3.88 g, absolute length 3.65 cm, specific growth rate 3,99%, survival rate 95 %, feed efficacy 83.25%, and feed convertion ratio 1.21. Hidrolitic enzyme had no effect on the survival rate. The water quality parameters recorded during in the research period ammonia (NH3) 0.0009-0.0022 mg/L, TAN 0.44-0.66 mg/L, temperature 26,1-31 0C, pH 5,4-6,50, dissolved oxygen (DO) 3,60-5,80 mg/L. The best growth of leavy vegetable (Ipomea reptan) obtained from enzyme 0 g/kg feed (P0) which is high 42,87 and 42,60 cm and weight 7,13 and 5,91 g.Key words: river catfish ,enzyme, growth, survival rate and recirculation.